Deepening the understanding of wreck ecology: a comparative study of marine sediment microbiomes across 10 Maltese wreck sites - Bolton, Emma; Greenhalgh, Nadine; Kunselman, Emily; Mifsud, Jasmine; Patel, Neem; Sausmekat, Maja Pace; Oldach, Phoebe; Gambin, Timmy (Frontiers in Marine Science, 2024)
The anthropogenic influences of historical shipwrecks on the marine environment remain largely uncharacterized, particularly for wrecks located at depths of 50 meters and lost over 80 years ago. Below 50 meters, the marine environment transitions from the euphotic to the mesophotic zone, where reduced light, significant changes in oxygen levels, and increased pressure may alter microbial communities and metabolic pathways. Understanding these shifts can provide insights into the adaptation and evolution of microorganisms. Sediment samples were collected by a team of divers from nine wreck sites off the coast of Malta, varying in depth from 5 to 100 meters. All sampling was conducted with the consent and authorization of the Government of Malta for the collection of marine genetic resources. Chemical analyses and metabarcoding techniques were employed to assess how shipwrecks influence microbial diversity and community composition in the surrounding sediments. Alpha (α) diversity of microbial communities was higher in sediments adjacent to the shipwrecks compared to those collected over 100 meters away from any wreck site. Across all nine wreck sites, sediment size emerged as the most significant driver of microbial diversity, followed by frame type and the presence of oil leaks. This study demonstrates that shipwrecks, varying in depth, frame type, and country of origin, significantly influence the microbial ecosystems and sediment chemistry of their surrounding environment. The findings suggest that shipwrecks act as focal points for ecological and chemical changes, contributing to the dynamic interactions between historical artifacts and marine ecosystems.